Models of Female Coolie Clothes in the Deli Tobacco Plantation of East Sumatra in 1863-1942 - Rosmaida Sinaga; Halimah Tusaddiah; Jussi Eka Ulitta Br Tarigan; Dora Irene Nababan; Ulung Napitu (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study aims to find out the background of the different models of women's coolie clothing in the Deli tobacco plantation and the factors that affect it. The method used is the Kuntowijoyo historical method with the stages of topic selection, heuristic, verification, interpretation, and historiography. The results of the study show that the background of different clothing models is influenced by differences in ethnic origin and economic conditions, so that female coolies continue to use clothes brought from their home regions. Chinese female coolies wear simple long-sleeved blouses, Javanese coolies wear kebaya with batik cloth or sarongs, and Indian coolies wear traditional sarees. In addition, the difference in clothing models was also influenced by low wages, social stratification in colonial society, and changes in roles from ordinary coolies to nyai. The novelty of this research lies in the use of colonial photo archives as the main source for studying women's coolie clothing models. This study describes the clothing of various ethnicities and analyzes the differences in clothing models between Chinese, Javanese, and Indian coolies. This approach provides a new perspective by placing clothing as a social representation related to ethnic identity, economic conditions, and social stratification in colonial-era plantations.